Análise de corrente de densidade em configuração de bacia com alimentação contínua - Santos, Litiéle dos (2020)
Density current flows occur due to the density difference between the two fluids. This density difference happens for several reasons, such as the temperature difference and the presence of particles in the flow. When the flow has suspended particles, this is a particular case of density currents, which are called turbidity currents. The study of these currents is essential for an understanding of sedimentary basins formation, which have an unconfined flow configuration. This configuration is still not deep studied in the literature, due to the difficulty of experimental instrumentation and the high computational cost of numerical simulation. Thus, the main goal is to identify and analyze the flow patterns and the deposited map formed by a density current in basin configuration with continuous inflow flow, using high precision numerical simulation. Incompact3D was used to perform Direct Numerical Simulation (DNS) and Implicit Large Scale Simulation (iLES). Different variables were analyzed, such as the position and velocity of the front’s current, in addition to deposit maps and the evolution of the shape of the density currents. From these analyzes, it was observed that the format developed by the unconfined current is directly related to the relationship between the inertial and viscous forces of the flow (know as the Reynolds number) and with the particle sedimentation velocity. Finally, it was still possible to relate the dynamics of the current to the deposited map formed and the erosive potential in the bed.